American wine economics : an exploration of the U.S. wine industry - Thornton, James Arthur, 1955- (University of California Press, 2013)
The U.S. wine industry is growing rapidly and wine consumption is an increasingly important part of American culture. American Wine Economics is intended for students of economics, wine professionals, and general readers who seek to gain a unified and systematic understanding of the economic organization of the wine trade. The wine industry possesses unique characteristics that make it interesting to study from an economic perspective. This volume delivers up-to-date information about complex attributes of wine; grape growing, wine production, and wine distribution activities.